RISIKO KREDIT DAN EFISIENSI PERBANKAN DI INDONESIA - Sparta Sparta (Universitas Mercu Buana, 2016)
Abstract: This Research goals are to examine and to analyze the level of banking efficiencyin Indonesia using SFA, to examine the impact of risk on bank efficiency in Indonesia, toexamine the effect of the control variables and specific macroeconomic banks to the level ofrisk and banking efficiency in Indonesia. The sample are 107 conventional banks inIndonesia and the number of observation in 1177 during the period 2001 to 2011. Efficiencymeasurement uses stochastic frontier approach bank and bank risk measurement uses the ratioof non-performing loans. The dependent variable used in the first study equation is nonperformingloans and in the second equation is the bank score efficiency. Control variablesare capital adequacy, asset growth, the percentage of foreign ownership, the percentage ofgovernment ownership, the percentage of public ownership, GDP growth and the bank loangrowth. The result shows that the average level of banking efficiency during the studyperiod is 69.98%. Overall the average level of conventional banks efficiency per yearincrease from 61.26% in 2001 to 78.76% in 2011. This study provides empirical evidencethat the risk of banks affect bank efficiency. Banks efficiency level are positively significantinfluenced mainly by the growth of GDP and the level of efficiency last year and negativelysignificant influenced by the bank risk. Empirical results of this study have implications forpractitioners banks, institutions banking authorities or the FSA and the development of thetheory of risk associated with relationship banks and banking efficiency as well asconsideration of other factors that influence risk and efficiency as the results of this study.Keywords: Bank risk, bank efficiency, stochastic frontier approach, bank capital adequace,Gross domestic BrutoAbstrak: Tujuan penelitian ini adalah untuk: 1). Menguji dan menganalisis tingkat efisiensiperbankan di Indonesia menggunakan SFA, 2). Menguji dampak dari risiko pada efisiensiperbankan di Indonesia, 3). menguji pengaruh variabel kontrol dan bank makroekonomikhusus untuk tingkat risiko dan perbankan efisiensi di Indonesia. Sampel adalah 107 bankkonvensional di Indonesia dan jumlah observasi di 1177 selama periode 2001 sampai 2011.Pengukuran effisien bank menggunakan pendekatan stochastic frontier dan pengukuranrisiko bank menggunakan rasio non-performing loan. Variabel dependen yang digunakandalam persamaan penelitian pertama adalah pinjaman non-performing dan persamaan keduaadalah skor Efisiensi Bank. variabel kontrol adalah kecukupan modal, pertumbuhan aset,persentase kepemilikan asing, persentase kepemilikan pemerintah, persentase kepemilikanpublik, pertumbuhan PDB dan pertumbuhan pinjaman bank. Hasil penelitian menunjukkanbahwa rata-rata tingkat perbankan efisiensi selama periode penelitian adalah 69,98%. Secarakeseluruhan rata-rata tingkat efisiensi bank konvensional per tahun meningkat dari 61,26% di2001-78,76% pada tahun 2011. Penelitian ini memberikan bukti empiris bahwa risiko bankmempengaruhi efisiensi perbankan. Tingkat efisiensi Bank signifikan positif dipengaruhiterutama oleh pertumbuhan PDB dan tingkat efisiensi tahun lalu dan signifikan negatifdipengaruhi oleh risiko bank. Hasil empiris penelitian ini memiliki implikasi bagi parapraktisi bank, lembaga otoritas perbankan atau FSA dan pengembangan teori risiko yang terkait dengan bank hubungan dan efisiensi perbankan serta pertimbangan faktor-faktor lainyang memengaruhi risiko dan efisiensi sebagai hasil dari penelitian ini .Kata kunci: Risiko Bank, Efisiensi Perbankan, Pendekatan Stochastic Frontier, Kecukupanmodal bank, Produk Domestic Bruto.